Pengaruh Disiplin Kerja dan Lingkungan Kerja Terhadap Kinerja Guru di SMP Negeri Se Kecamatan Simpangkatis - Nafisah Nafisah; Yasir Arafat; Nur Ahyani (Journal on Education, 2023)
The abstract should be clear, concise, and descriptive. This study was conducted with the aim of knowing whether or not there is an influence between the teacher's social competence on Muhammadiyah 1 Surakarta high school learning achievement. Failure to achieve good learning achievement shows the lack of success of an educational process. It is expected that with efforts to apply good and appropriate social competence, it is hoped that students' Muhammadiyah learning achievement will be achieved well and satisfactorily. The method used in this research is quantitative-correlational. The population in this study were all grade X students at SMA Muhammadiyah 1 Surakarta, totaling 208 students. Data collection techniques chosen by researchers are observation, interviews, questionnaires and documentation studies. Data analysis techniques in this study used descriptive analysis and simple linear regression analysis with the help of SPSS software in processing the data obtained. The results showed that: 1) The social competence of teachers at SMA Muhammadiyah 1 Surakarta shows a percentage of 69% with a moderate category; 2) Then for Muhammadiyah learning achievement in SMA Muhammadiyah 1 Surakarta shows a percentage of 40% with a low category; 3) Based on the results of hypothesis testing that has been carried out, it shows that r count 0.241> r table 0.235 which means that there is a significant influence between the social competence of teachers on Muhammadiyah learning achievement at SMA Muhammadiyah 1 Surakarta with a variable contribution of teacher social competence of 5.8% to Muhammadiyah learning achievement.